Investigation of latent heat storage performance of a solar collector incorporating dimpled dendritic fins and nano-additive phase change material - Gursoy, Emrehan; Kaya, Hüseyin; Gürdal, Mehmet; Gedik, Engin (Pergamon-Elsevier Science Ltd, 2026)
In this numerical study, the melting and thermal energy storage performance of phase change material (PCM) integrated into flat-plate solar collector (FPSC) was investigated using dendritic fins with different dimple geometries (spherical, elliptical, trapezoidal), Fe3O4 nanoparticles at different volume concentrations (q = 0.5, 1.0, 2.0, 3.0 vol%), and metal foam (MF). The low thermal conductivity of PCMs limits the performance of latent heat thermal energy storage (LHTES) systems by prolonging the phase change periods. Therefore, the study aims to optimize the thermal performance by combining the effects of MF, which increases the effective thermal conductivity of the system, dendritic fins that increase the heat transfer surface area, and nanoparticles that improve the thermophysical properties. Numerical computations were managed under the condition of constant heat flux of q = 1000 W m- 2 using the enthalpy-porosity method and the local thermal equilibrium approach in ANSYS Fluent software. Analyses were conducted for total of 25 different cases. The results showed that the addition of nanoparticles suppressed natural convection, decreasing the melting performance, while dimpled dendritic fins increased the melting rate by 79 %. The highest melting rate was achieved with trapezoidal dimpled dendritic fins (complete melting in 21 min). Furthermore, the highest stored energy of 279 kJ kg- 1 was obtained with spherical dimpled dendritic fins. The novelty of this study is the use of dimpled dendritic fins for the first time in literature and their integration into FPSC as hybrid system with MF + nano-PCM. This design contributes to the development of next-generation compact and high-efficiency LHTES systems.
Keywords: Dimpled dendritic fins; Energy storage; Nano-additive phase change materials; Solar collector